The Retirement Plan Dilemma: Who Is Best Prepared for Retirement in Today’s Environment? - Zhang, Yu; Li, Xun; Lawrence, Shari; Chiasson, Andrea (Journal of Accounting and Finance, 2024)
This study examines the factors affecting retirement preparation through employer-sponsored retirement plans using the Survey of Consumer Finances’ (SCF) 2019 data. Various socio-economic and demographic variables are analyzed for significance regarding employee participation in and contributions to employer sponsored retirement plans. Our results indicate that gender, marital status, age, race, financial literacy, risk tolerance, inheritance expectation, and income are all important factors that affect plan participation rates as well as contribution levels. For minority women, income appears to be the most crucial factor in increasing participation. The results provide some implications for policymakers about improving retirement plan policies for women and minorities. The findings may also help individuals make better retirement planning decisions, especially in the face of possible social security benefit shortages and pension plan changes. This study is of great importance, as current retirement plans place a greater responsibility on both employers and individuals for retirement planning.